(untitled) (Journal of Philosophy Culture and Political Science, 2018)
In this article authors analyse history forming and development of logic in ancient philosophy beginning from sophists to traditional logic of Aristotle. Certainly in one article to expose a complete picture ancient philosophy it is impossible on the whole, on this basis we separately distinguish the logical reflections of the known thinkers of that period as Protagoras, Gorgias, Prodicus and other sophists. And also in the article the special place is distinguished to dialectics of Heraclitus, grounded his studies about contradictions. Authors also prove that, the studies of Plato and his teacher Socrates consist not of elemental application of formally-logical rules. If sophists arbitrarily operated concepts and terms, then Socrates and Plato opened out with them a fight, in that tried to defend native, correct senses of words expressing main spiritual universal. It becomes firmly established that they put beginning the same to procedure of determination, or definition. Key words: history of philosophy, logic, sophistry, dialectics, sophists, maieutics, substance, rhetoric.